Sediments and Seashores - A Case Study of Local Citizen Science Contributing to Student Learning and Environmental Citizenship - Carson, Sally; Rock, Jenny; Smith, Jeffery (Frontiers in Education, 2021)
Citizen science aims to bridge the gap between science and society by engaging people in understanding the process of science. This is needed to foster informed democratic involvement of critical, environmentally informed citizens. Can these aspirations be facilitated by school-based citizen science that offers opportunity to engage scientifically with environmental issues at a scale with local relevance? This is tested through application of Marine Metre Squared (Mm2), a citizen science initiative for long-term monitoring of the New Zealand intertidal zone. Through direct observation and ‘hands-on’ engagement, participants are involved in place-based learning that connects them with nature. Strong interest from teachers and uptake into school programmes has been key to its success in collecting long term biodiversity data. Through facilitated delivery, the project also has the capacity to meet school curriculum goals and develop the environmental science citizenship capabilities of participants. Assessing the use of Mm2 as a citizen science intervention within schools, we found that it effected science learning, skill development and environmental attitudes. Our findings further demonstrate the effect of extended involvement in a citizen science project, the value of a local issue-focused project for student learning outside the classroom, and how school science education can be enriched through citizen science to also grow civic responsibility for the environment (environmental citizenship).